Treatment and outcomes of arthrogryposis in the lower extremity. Issue 3 (3rd September 2019) - Hamdy, Reggie C.; van Bosse, Harold; Altiok, Haluk; Abu‐Dalu, Khaled; Kotlarsky, Pavel; Fafara, Alicja; Eidelman, Mark
Abstract: In this multiauthored article, the management of lower limb deformities in children with arthrogryposis (specifically Amyoplasia) is discussed. Separate sections address various hip, knee, foot, and ankle issues as well as orthotic treatment and functional outcomes. The importance of very early and aggressive management of these deformities in the form of intensive physiotherapy (with its various modalities) and bracing is emphasized. Surgical techniques commonly used in the management of these conditions are outlined. The central role of a multidisciplinary approach involving all stakeholders, especially the families, is also discussed. Furthermore, the key role of functional outcome tools, specifically patient reported outcomes, in the continuous monitoring and evaluation of these deformities is addressed. Children with arthrogryposis present multiple problems that necessitate a multidisciplinary approach. Specific guidelines are necessary in order to inform patients, families, and health care givers on the best approach to address these complex conditions